Pembelajaran Sains Untuk Mengenalkan Kebencanaan Pada Anak Usia Dini - Rahma, Aldila (Jurnal Golden Age, 2020)
Children are one of the most disaster-prone community members due to their limited experience, knowledge, and physical. Therefore, children must be introduced as early as possible about disaster knowledge through education at school. Teaching and learning of disaster material can be done through science learning activities. This article aims to describe various methods and science learning activities, which are fun and attractive to convey disaster knowledge comprehend by children. This paper using a qualitative method approach with document study research types. An introduction of disaster knowledge to children in schools is a part of nonstructural mitigation efforts through education